Test Suite Minimization using Hybrid Algorithm for GA generated Test Cases - Maragathavalli, Mrs. P; Kanmani, S. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Software testing and retesting occurs continuously during the software development lifecycle to detect errors as early as possible. As the software evolves the size of test suites also grows. When the no of test cases generated are more, obviously size of the test suite will also be more.Â  So the testing time is to be minimized by reducing the execution time of the algorithm used for test data generation and also by introducing minimization procedure for test suite reduction. Due to limited resources and timing constraints for testing, test suite minimization techniques are needed to eliminate redundant test cases as possible. By considering multiple objectives rather than the coverage alone, the test cases are being generated which satisfies the testing requirements. Most of the existing techniques are code-based. In this article we present an approach by modifying an existing heuristic for test suite minimization.Â  Genetic algorithm has been used for random test data generation and the output of GA is given to the minimization procedure for reducing the total no of generated test cases, collectively named as Hybrid Algorithm (HA). The results are satisfactory and show significant improvements in reducing test suite size with minimum execution time. Experiments have been done for simple to medium complexity java programs taken from SIR and execution time is reduced to 5,685ms for a test set. The results are compared with existing method Mutant Gene Algorithm and size of test suite is minimized upto 13.6% using Hybrid Algorithm.